Analisis Kelayakan Usaha Sayuran Selada (Lactuca Sativa, L) Hidroponik di PT XX Kabupaten Tanggamus, Provinsi Lampung - Kusmaria Kusmaria; Annisa Fitri; Sudiyo Sudiyo; Depita Anggraini (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2021)
Horticultural commodities (vegetables and fruit) are one of the commodities that have the potential to be cultivated and can be an alternative income for agribusiness entrepreneurs, considering the lifestyle of today's people who are increasingly inclined to a healthy lifestyle by consuming lots of fruits and vegetables. Moreover, currently growing vegetables can be applied through a limited garden hydroponically. This study aims to see the feasibility of hydroponic vegetable business at PT. XX, Tanggamus Regency, Lampung Province. The research was conducted at PT. XX in August 2021, the type of data used is time series data, namely company data operating in the last two years, and the data collection method is by interview (survey). Data analysis was carried out by measuring feasibility aspects which included NPV, IRR, Net B/C/BEP and Payback Period. The results of the analysis show that the calculation of NPV at PT. XX has a positive value of Rp. 648,421,649.95, the IRR value is 34%, Net B/C shows the number 1.27, BEP 4 years 10 months 19 days, and PBP 2 years 2 months 6 days. From the results of these calculations it can be concluded that the hydroponic vegetable business at PT. XX is worth running.